2005
DOI: 10.1177/1368430205053940
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it to Ourselves: Effects of Audience Size and Composition on Reactions to Criticisms of the Ingroup

Abstract: Criticism is an important aspect of communication within and between groups, but reactions to criticism of groups have been little studied. Past research has shown that criticism elicits greater sensitivity when made by an outgroup member, compared to an ingroup member. Two experiments were conducted to examine how this intergroup sensitivity effect (ISE) is affected by the context of the criticism. Experiment 1 showed that the ISE occurs in a private context, but disappears when it is clear that the criticism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…Examples of this dissociation across response dimensions can be found in the literature on the role of audiences in moderating responses to criticism. As stated above, ingroup critics who take their comments to an outgroup audience tend to be seen as less likeable and tend to face heightened negativity than those who keep their comments in-house (Ariyanto et al, 2006;Elder et al, 2005;Hornsey et al, 2005). Interestingly, however, violations of this ''in-house'' rule do not appear to influence attributions of motive, and do not influence whether group members are willing to agree with the criticisms.…”
Section: The Current Studymentioning
confidence: 64%
See 1 more Smart Citation
“…Examples of this dissociation across response dimensions can be found in the literature on the role of audiences in moderating responses to criticism. As stated above, ingroup critics who take their comments to an outgroup audience tend to be seen as less likeable and tend to face heightened negativity than those who keep their comments in-house (Ariyanto et al, 2006;Elder et al, 2005;Hornsey et al, 2005). Interestingly, however, violations of this ''in-house'' rule do not appear to influence attributions of motive, and do not influence whether group members are willing to agree with the criticisms.…”
Section: The Current Studymentioning
confidence: 64%
“…One such rule is to always keep your criticisms ''in-house'' (''Don't air your dirty laundry''). Indeed, ingroup critics who violate this rule tend to be seen as less likeable and tend to face heightened negativity (Ariyanto, Hornsey, & Gallois, 2006;Elder, Sutton, & Douglas, 2005;Hornsey, de Bruijn, Creed, Allen, Ariyanto, & Svensson, 2005).…”
Section: Social Conventions and Responses To Group Criticismmentioning
confidence: 96%
“…Research has shown that ingroup criticism is likely to be evaluated as socially acceptable and conventional, as well as legitimate and constructive, so long as it can be perceived as a suggestion for improvement (Hornsey, Oppes, & Svensson, 2002;Hornsey & Imani, 2004). However, this constructive effect of criticism only occurs when the group is criticized to an exclusively ingroup audience, and not when the group is criticized in front of an outgroup audience (Elder, Sutton, & Douglas, 2005;Hornsey et al, 2005;Ariyanto, Hornsey, & Gallois, 2006). Reporting an ingroup misconduct to outside persons or authorities is a violation of the implicit rule that group members should never criticize their own group to outsiders.…”
Section: Reporting Transgressions Within Groupsmentioning
confidence: 99%
“…For example, research has demonstrated that criticism from an ingroup source is perceived negatively when it is communicated to an outgroup audience (Ariyanto, Hornsey, & Gallois, 2006;Elder, Sutton, & Douglas, 2005;. The negativity presumably comes from the fact that "airing dirty laundry" to outgroup members breaches the rules of strategic image management.…”
Section: Studymentioning
confidence: 99%